Shaped phase change material, preparation method thereof and shaped phase change material film

By using a porous skeleton and specific adhesive in the shaped phase change material, the phase change core material is adsorbed, which solves the problem that existing materials cannot have both low leakage, high load and high flexibility, and achieves higher comprehensive performance.

CN119592048APending Publication Date: 2025-03-11THERO NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411764141.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing fixed phase change materials cannot have both low leakage, high load and high flexibility, limiting their application scenarios.

Method used

The phase change core material is adsorbed by using porous skeletons and adhesives such as polyurethane, epoxy resins and silicone to form a porous skeleton with high porosity, reducing leakage of the phase change core material and improving its load capacity.

Benefits of technology

Low leakage, high load and high flexibility of the fixed phase change material is achieved, improving its comprehensive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592048A_ABST
    Figure CN119592048A_ABST
Patent Text Reader

Abstract

The invention provides a shaped phase-change material, a preparation method thereof and a shaped phase-change material film, and relates to the technical field of phase-change energy storage, the shaped phase-change material comprises a porous skeleton and a phase-change core material adsorbed on the porous skeleton; wherein the porous framework comprises a porous adsorbent and an adhesive, and the phase change core material comprises an energy storage material; the adhesive comprises at least one of polyurethane, epoxy resin and silica gel. The shape-stabilized phase change material provided by the embodiment of the invention has the advantages of low leakage, high load and high flexibility, and the comprehensive performance of the shape-stabilized phase change material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of phase change energy storage technology, and in particular to a shaped phase change material and a preparation method thereof, and a shaped phase change material film. Background Art

[0002] With the acceleration of global energy transformation and the popularization of low-carbon economy, energy storage technology is becoming increasingly important as the key to solving the intermittent and instability problems of new energy. Among them, phase change energy storage is one of the research hotspots in the field of energy storage technology. It has a series of advantages such as high energy storage density, good temperature uniformity during phase change process, high safety, and reusability. It is often used in aerospace, power plant peak shifting, household appliance development and other application fields, as well as the storage of various energy sources such as electricity, solar energy, wind energy, ocean energy, and industrial waste heat. Solid-liquid phase change energy storage has been widely used in industrial applications due to its advantages such as large phase change latent heat and stable performance, but it still has problems such as low thermal conductivity, slow heat storage and release, and easy leakage during phase change.

[0003] The shaped phase change material can absorb the phase change core material in the microporous structure through the adsorbent, and the adsorbent can also play a role in shaping the skeleton. The phase change core material forms a mesh structure in the skeleton, which has the advantages of high thermal conductivity and low leakage. However, the shaped phase change material in the related art still cannot have low leakage, high load and high flexibility, which limits its application scenarios. Summary of the invention

[0004] The embodiments of the present application provide a shaped phase change material and a preparation method thereof, and a shaped phase change material film, which can have low leakage, high load and high flexibility, and improve the comprehensive performance of the shaped phase change material.

[0005] In a first aspect, an embodiment of the present application provides a shaped phase change material, comprising a porous skeleton and a phase change core material adsorbed on the porous skeleton;

[0006] Wherein, the porous skeleton includes a porous adsorbent and a binder, and the phase change core material includes an energy storage material;

[0007] The adhesive includes at least one of polyurethane, epoxy resin and silicone.

[0008] Optionally, the mass ratio of the porous adsorbent to the phase change core material is (1-3):(8-9).

[0009] Optionally, the mass ratio of the adhesive to the phase change core material is (1-3):(7-9).

[0010] Optionally, the porous adsorbent includes at least one of activated carbon, biochar, diatomaceous earth, attapulgite, montmorillonite and graphene.

[0011] Optionally, the polyurethane comprises at least one of a single-component polyurethane and a multi-component polyurethane;

[0012] And / or, the silica gel includes at least one of single-component silica gel and multi-component silica gel.

[0013] Optionally, the energy storage material includes at least one of nitrates, sulfates, carbonates, acetates, chlorides, bromides and borates.

[0014] Optionally, the phase change core material further includes at least one of a nucleating agent, a stabilizer and a thermal conductive aid.

[0015] Optionally, the mass ratio of the energy storage material to the thermal conductive additive is (8-10): (0-2).

[0016] Optionally, the nucleating agent includes at least one of polyethylene, talc, mica, borax and phosphate;

[0017] and / or, the stabilizer comprises at least one of xanthan gum, sodium methyl cellulose and sodium polyacrylate;

[0018] And / or, the thermal conductive additive includes at least one of carbon nanotubes, graphene, organic silicon compounds and nano oxides.

[0019] In a second aspect, an embodiment of the present application provides a method for preparing a shaped phase change material, comprising:

[0020] Provide phase change core material;

[0021] mixing a porous adsorbent and a binder with a phase change core material to obtain a first mixture;

[0022] The first mixture is subjected to a heating treatment and then subjected to a vacuum adsorption treatment to obtain a pretreated material;

[0023] The pretreated material is transferred to a mold, subjected to compression molding and solidification, to obtain a shaped phase change material.

[0024] Optionally, after providing the phase change core material, the method further comprises:

[0025] The phase change core material is ground to 5μm-20μm.

[0026] Optionally, the first mixture is subjected to a heat treatment, comprising:

[0027] Heating the first mixture at a first heating temperature for 20 min to 50 min;

[0028] Among them, the first heating temperature is T 1 , the highest phase change temperature of the energy storage material in the phase change core material is T 2 , 30℃≤T 1 -T 2 ≤50℃.

[0029] Optionally, a vacuum adsorption treatment is performed, including:

[0030] The heated first mixture is maintained under a vacuum condition of 0.1 MPa-1.0 MPa for 15 min-30 min.

[0031] Optionally, curing comprises:

[0032] Curing at room temperature for 12h-24h.

[0033] In a third aspect, an embodiment of the present application further provides a shaped phase change material film, comprising a base film and a protective film coated on the periphery of the base film;

[0034] Wherein, the base film is made of the fixed-shape phase change material as described above, and / or is made of the fixed-shape phase change material preparation method as described above.

[0035] Optionally, the material of the protective film includes at least one of single-component polyurethane, multi-component polyurethane, epoxy resin, single-component silicone and multi-component silicone.

[0036] Beneficial effects of the embodiments of the present application:

[0037] The shaped phase change material provided in the embodiment of the present application can bond and connect the porous adsorbent through an adhesive to form a porous skeleton with high porosity. The porous skeleton can adsorb the phase change core material containing the energy storage material into its porous structure, reduce the leakage problem of the phase change core material during the phase change process, and improve the load capacity of the phase change core material. Among them, the adhesive includes at least one of polyurethane, epoxy resin and silica gel. This type of adhesive has strong flexibility and ductility, so that the shaped phase change material has good flexibility and ductility. That is, the shaped phase change material provided in the embodiment of the present application can have low leakage, high load and high flexibility, and improve the comprehensive performance of the shaped phase change material. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0039] Figure 1 is the differential scanning calorimetry diagram of Example 1 provided in the present application;

[0040] Figure 2 is the differential scanning calorimetry diagram of Example 2 provided in the present application;

[0041] Figure 3 is the differential scanning calorimetry diagram of Example 3 provided in the present application;

[0042] Figure 4 is the differential scanning calorimetry diagram of Example 4 provided in the present application;

[0043] Figure 5 is the differential scanning calorimetry diagram of Example 5 provided in the present application;

[0044] Figure 6 is the differential scanning calorimetry diagram of Example 6 provided in the present application;

[0045] Figure 7 is the differential scanning calorimetry diagram of Comparative Example 1. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0047] In a first aspect, an embodiment of the present application provides a shaped phase change material, comprising a porous skeleton and a phase change core material adsorbed on the porous skeleton. The porous skeleton comprises a porous adsorbent and an adhesive, and the phase change core material comprises an energy storage material. The adhesive comprises at least one of polyurethane, epoxy resin and silica gel.

[0048] In the shaped phase change material provided in the embodiment of the present application, the porous adsorbent can be bonded and connected by an adhesive to form a porous skeleton with high porosity. The porous skeleton can adsorb the phase change core material containing the energy storage material into its porous structure, reduce the leakage problem of the phase change core material during the phase change process, and improve the load capacity of the phase change core material. Among them, the adhesive includes at least one of polyurethane, epoxy resin and silica gel. This type of adhesive has strong flexibility and ductility, so that the shaped phase change material has good flexibility and ductility. That is, the shaped phase change material provided in the embodiment of the present application can have low leakage, high load and high flexibility, and improve the comprehensive performance of the shaped phase change material.

[0049] In addition, the porous skeleton can provide a good heat conduction path, which helps to quickly transfer heat in the shaped phase change material, thereby improving the energy storage efficiency.

[0050] Among them, energy storage materials refer to materials that can store energy. These materials have specific physical, chemical or biological properties and can absorb, store and release energy when needed.

[0051] The adhesive includes at least one of polyurethane, epoxy resin and silicone. Polyurethane, epoxy resin and silicone have high mechanical strength, excellent elastic modulus, good processing performance and bonding performance. On the basis of bonding the porous adsorption material to form a porous skeleton, the overall flexibility and structural strength can be improved, and the processing process is relatively simple. In addition, polyurethane, epoxy resin and silicone have good chemical stability, which can ensure the stability of the fixed phase change material.

[0052] In some embodiments, the mass ratio of the porous adsorbent to the phase change core material is (1-3):(8-9).

[0053] By setting the mass ratio of the porous adsorbent to the phase change core material to (1-3): (8-9), the loading capacity of the shaped phase change material can be improved. That is, by loading a larger proportion of the phase change core material on the porous adsorbent, the shaped phase change material can store more phase change latent heat, thereby improving the thermal energy storage and release efficiency of the shaped phase change material. Furthermore, by setting the mass ratio of the porous adsorbent to the phase change core material within the above range, it can also ensure that the phase change core material is fully adsorbed in the pores of the porous adsorbent, thereby reducing the leakage problem of the phase change core material.

[0054] In some embodiments, the mass ratio of the binder to the phase change core material is (1-3):(7-9).

[0055] Similarly, by setting the mass ratio of the adhesive to the phase change core material to (1-3): (7-9), the proportion of the phase change core material in the fixed phase change material can be ensured, so that the fixed phase change material can store more phase change latent heat. In addition, within this mass ratio range, it can be ensured that there is enough adhesive to bond the phase change core material to the porous adsorbent, ensuring bonding stability.

[0056] In some embodiments, the porous adsorbent includes at least one of activated carbon, biochar, diatomaceous earth, attapulgite, montmorillonite and graphene. Among them, activated carbon and biochar have high specific surface area and excellent adsorption performance, and the source of biochar is wide and renewable. Diatomaceous earth has the characteristics of high porosity, light weight, and softness, and it has good stability and thermal properties as a carrier. Atriolith and montmorillonite are layered silicate minerals with good thermal conductivity and stability. Graphene is a two-dimensional material composed of carbon atoms with extremely high thermal conductivity and mechanical strength. As a porous adsorbent for a shaped phase change material, it can improve heat transfer efficiency and improve phase change behavior.

[0057] In some embodiments, the polyurethane includes at least one of a one-component polyurethane and a multi-component polyurethane.

[0058] Among them, one-component polyurethane is usually made by dehydrating mixed polyethers, adding diisocyanates and additives for epoxy modification. Single components do not need to be mixed, which can simplify the operation steps and has a faster curing speed. Multi-component polyurethane refers to a polyurethane composed of at least two components. When used, more than two components need to be prepared in a certain proportion. Compared with one-component polyurethane, multi-component polyurethane can adjust parameters such as curing speed, hardness and strength by mixing different components to meet the needs of different scenarios. The interaction between different components in multi-component polyurethane can provide stronger adhesion, excellent weather resistance, and can maintain stable performance over a wide temperature range.

[0059] The multi-component polyurethane may be a two-component polyurethane, a three-component polyurethane, etc. For example, the two-component polyurethane may be composed of a DSR-201A component and a DSR-201B component, and the mass ratio of the two may be (0-1):(9-10), and the supplier is Shenzhen Paiholl Technology Co., Ltd.

[0060] In some embodiments, the silica gel includes at least one of a single-component silica gel and a multi-component silica gel.

[0061] Among them, single-component silicone is usually mainly composed of polysiloxane polymerization and is a single polymer material. Single-component silicone has high temperature resistance, good weather resistance, good corrosion resistance, and excellent bonding performance. Multi-component silicone is obtained by mixing two or more different materials, usually including silicate, silicon propane and catalyst. Compared with single-component silicone, multi-component silicone usually has better flexibility and deformation ability, and stronger high temperature resistance.

[0062] In some embodiments, the energy storage material includes at least one of nitrates, sulfates, carbonates, acetates, chlorides, bromides and borates. Such materials can absorb or release a large amount of heat during melting or solidification, and have good application prospects in the fields of energy storage, temperature control, etc.

[0063] In some embodiments, the phase change core material also includes at least one of a nucleating agent, a stabilizer, and a thermal conductive aid. By adding at least one of a nucleating agent, a stabilizer, and a thermal conductive aid to the phase change core material, the performance and application effect of the phase change core material can be improved. Specifically, the nucleating agent can accelerate the crystallization rate of the energy storage material, which is for rapid response to temperature changes. The nucleating agent can also improve the mechanical properties and thermal properties of the material, and improve the physical and mechanical properties. The stabilizer can enhance the stability of the energy storage material at high temperatures, prevent the material from decomposing or deteriorating during heating, prevent the phase change core material from phase separation during long-term use, and ensure the uniformity and stability of the material. The thermal conductive aid can increase the thermal conductivity of the phase change core material, accelerate the heat transfer rate in the material, optimize thermal management, and enhance thermal uniformity.

[0064] In some embodiments, the mass ratio of the energy storage material to the thermal conductive additive is (8-10): (0-2). That is, a higher proportion of the energy storage material helps the phase change core material store more phase change latent heat and achieve efficient energy storage and release. By controlling the mass ratio of the energy storage material to the thermal conductive additive within the above range, it is possible to optimize the comprehensive performance of the device, such as thermal conductivity and mechanical properties, while ensuring the basic energy storage performance of the phase change core material.

[0065] In some embodiments, the nucleating agent includes at least one of polyethylene, talc, mica, borax and phosphate. Among them, polyethylene is a high molecular weight material, and the polyethylene particles that have been modified or micronized have a nucleating effect. Talc is a natural layered silicate mineral with good lubricity, dispersibility and chemical stability. As a nucleating agent, it can effectively promote the crystallization of energy storage materials, refine grains, and improve thermal stability and mechanical properties. Mica is also a layered silicate mineral that can provide a large number of nucleation sites to promote the rapid crystallization of energy storage materials. Borax is an inorganic compound with good chemical stability, which can provide abundant nucleation sites and can also improve the corrosion resistance of phase change core materials. Phosphate, as a nucleating agent, can provide nucleation sites and has good thermal stability and chemical stability.

[0066] In some embodiments, the stabilizer includes at least one of xanthan gum, sodium methyl cellulose and sodium polyacrylate. Among them, xanthan gum has excellent thickening, suspension and stability. In the phase change core material, xanthan gum can form a three-dimensional network structure, which can effectively wrap and fix the energy storage material and reduce the leakage or migration of the material. And xanthan gum also has good temperature resistance and salt resistance, and can maintain stable performance in a wide temperature range and chemical environment. Sodium methyl cellulose is a water-soluble cellulose ether. As a stabilizer in the phase change core material, it can form a protective film on the surface of the energy storage material through its film-forming properties, reducing the pollution and erosion of the material by external impurities. Sodium methyl cellulose also has certain water retention and lubricity, which helps to improve the processing performance of the phase change core material. Sodium polyacrylate is a polymer electrolyte with good water absorption, water retention and dispersibility. In the phase change core material, sodium polyacrylate, as a stabilizer, can absorb and fix the moisture in the energy storage material through its water absorption, preventing the evaporation of water from causing its performance to decline.

[0067] In some embodiments, the thermal conductive aid includes at least one of carbon nanotubes, graphene, organosilicon compounds and nano-oxides. Among them, carbon nanotubes have extremely high thermal conductivity, good mechanical properties and chemical stability. Graphene also has extremely high thermal conductivity, and its two-dimensional structure makes its specific surface area larger, which helps to form a good interface contact with the energy storage material, thereby improving the heat transfer efficiency. Organosilicon compounds are a class of organic compounds containing silicon elements, which usually have good thermal stability and chemical stability. The thermal conductivity can be improved by the interaction between the groups in the organosilicon compounds and the energy storage material. Nano-oxides, such as aluminum oxide, zinc oxide, etc., have high thermal conductivity and chemical stability, and can improve the heat transfer efficiency.

[0068] In a second aspect, an embodiment of the present application provides a method for preparing a shaped phase change material, comprising:

[0069] Provide phase change core material;

[0070] mixing a porous adsorbent and a binder with a phase change core material to obtain a first mixture;

[0071] The first mixture is subjected to a heating treatment and then subjected to a vacuum adsorption treatment to obtain a pretreated material;

[0072] The pretreated material is transferred to a mold, subjected to compression molding and solidification, to obtain a shaped phase change material.

[0073] In the embodiment of the present application, a phase change core material is mixed with a porous adsorbent and an adhesive to form a first mixture. The first mixture is then heated to mix and disperse the materials, and then subjected to vacuum adsorption treatment to adsorb the phase change core material in the pores of the porous adsorbent to obtain a pretreated material. The pretreated material is transferred to a suitable mold, subjected to compression molding and solidification, to form a directional phase change material of a specific shape.

[0074] In some embodiments, after providing the phase change core material, the method further comprises:

[0075] The phase change core material is ground to 5μm-20μm.

[0076] By grinding the phase change core material to 5 μm-20 μm, the dispersion performance of the phase change core material in the subsequent steps can be improved, and it is helpful for the phase change core material to be adsorbed into the pores of the porous adsorbent.

[0077] In some embodiments, heating the first mixture comprises:

[0078] Heating the first mixture at a first heating temperature for 20 min to 50 min;

[0079] Among them, the first heating temperature is T 1 , the highest phase change temperature of the energy storage material in the phase change core material is T 2 , 30℃≤T 1 -T 2 ≤50℃.

[0080] That is, during the heating process, making the heating temperature 30°C-50°C higher than the phase change temperature of the energy storage material can improve the completeness of the phase change of the energy storage material, change the density, volume, thermal conductivity, etc. of the energy storage material, and is not likely to cause problems such as a decrease in the thermal stability and durability of the energy storage material.

[0081] In some embodiments, a vacuum adsorption process is performed, including:

[0082] The heated first mixture is maintained under a vacuum condition of 0.1 MPa-1.0 MPa for 15 min-30 min.

[0083] In some embodiments, curing comprises:

[0084] Curing at room temperature for 12h-24h.

[0085] In a third aspect, the embodiments of the present application further provide a fixed phase change material film, comprising a base film and a protective film coated on the periphery of the base film, wherein the base film is made of the fixed phase change material as described above, and / or is made of the fixed phase change material preparation method as described above.

[0086] The protective film wrapped around the periphery of the base film can improve the waterproof performance of the fixed phase change material film, reduce the leakage problem of the base film during the phase change process, and extend the service life of the fixed phase change material film.

[0087] In some embodiments, the material of the protective film includes at least one of single-component polyurethane, multi-component polyurethane, epoxy resin, single-component silicone and multi-component silicone. Single-component polyurethane, multi-component polyurethane, epoxy resin, single-component silicone and multi-component silicone all have good flexibility and ductility. When such materials are used to prepare the protective film, the protective effect is improved while the overall flexibility and ductility of the fixed phase change material film are not affected.

[0088] The technical solution of the present application is introduced below in conjunction with specific embodiments:

[0089] Example 1

[0090] (1) 40.3 g of sodium acetate, 0.5 g of borax, 0.2 g of sodium polyacrylate, and 1.0 g of sodium methylcellulose were placed in a mortar and thoroughly mixed and ground to obtain a phase change core material with a particle size of 5 to 20 μm;

[0091] (2) The phase change core material was transferred to a ceramic crucible, 23 g of attapulgite and 34.7 g of polyurethane were added and stirred evenly, and then placed in a 90° C. hot water bath for heating and heat preservation for 30 min; then placed in a 0.6 MPa vacuum pot for evacuation for 20 min to obtain a pretreated material;

[0092] (3) Transfer the pretreated material to a 25mm*20mm*1.5mm mold for compression molding, wait for 12 hours at room temperature and then demold, to obtain a 25mm*20mm*1.5mm shaped phase change material.

[0093] Example 2

[0094] (1) 36.4 g of sodium acetate, 1.26 g of disodium hydrogen phosphate, 4.20 g of sodium bromide, and 1.56 g of nano copper oxide were placed in a mortar and thoroughly mixed and ground to obtain a phase change core material with a particle size of 5 to 20 μm;

[0095] (2) The phase change core material was transferred to a ceramic crucible, 23.17 g of attapulgite and 34.7 g of polyurethane were added and stirred evenly, and then placed in a water bath heated at 80° C. and kept warm for 30 min; then placed in a vacuum pot at -1.0 MPa and evacuated for 20 min to obtain a pretreated material;

[0096] (3) Transfer the pretreated material to a 25mm*20mm*1.5mm mold for compression molding, wait for 12 hours at room temperature and then demold, to obtain a 25mm*20mm*1.5mm shaped phase change material.

[0097] Example 3

[0098] (1) 34.25 g of sodium acetate, 1.26 g of borax, 6.30 g of sodium bromide, and 2.35 g of graphene were placed in a mortar and thoroughly mixed and ground to obtain a phase change core material with a particle size of 5 to 20 μm;

[0099] (2) The phase change core material was transferred to a ceramic crucible, 23.17 g of attapulgite and 34.7 g of multi-component polyurethane were added and stirred evenly, and then placed in a 90° C. hot water bath for heating and heat preservation for 30 min; then placed in a -1.0 MPa vacuum pot for evacuation for 20 min to obtain a pretreated material;

[0100] (3) Transfer the pretreated material to a 25mm*20mm*1.5mm mold for compression molding, wait for 12 hours at room temperature and then demold, to obtain a 25mm*20mm*1.5mm shaped phase change material.

[0101] Example 4

[0102] (1) 41.06 g of sodium sulfate decahydrate and 0.5 g of borax were placed in a mortar and thoroughly mixed and ground to obtain a phase change core material with a particle size of 5 to 20 μm;

[0103] (2) The phase change core material was transferred to a ceramic crucible, 23.44 g of attapulgite and 34.7 g of polyurethane were added and stirred evenly, and then placed in a 90° C. hot water bath for heating and heat preservation for 30 min; then placed in a -1.0 MPa vacuum pot for evacuation for 20 min to obtain a pretreated material;

[0104] (3) Transfer the pretreated material to a 25mm*20mm*1.5mm mold for compression molding, wait for 12 hours at room temperature and then demold, to obtain a 25mm*20mm*1.5mm shaped phase change material.

[0105] Example 5

[0106] (1) 41.06 g of sodium acetate, 0.50 g of borax, and 5 g of tetrabutyl sodium bromide were placed in a mortar and thoroughly mixed and ground to obtain a phase change core material with a particle size of 5 to 20 μm;

[0107] (2) The phase change core material was transferred to a ceramic crucible, 23.17 g of attapulgite and 34.7 g of polyurethane were added and stirred evenly, and then placed in a 90°C hot water bath for heating and heat preservation for 30 minutes; then placed in a vacuum pot at -1.0 MPa for 20 minutes to obtain a pretreated material;

[0108] (3) Transfer the pretreated material to a 25mm*20mm*1.5mm mold for compression molding, wait for 12 hours at room temperature and then demold, to obtain a 25mm*20mm*1.5mm shaped phase change material.

[0109] Example 6

[0110] (1) 36.4 g of sodium acetate, 1.26 g of borax, and 4.20 g of sodium chloride were placed in a mortar and thoroughly mixed and ground to obtain a phase change core material with a particle size of 5 to 20 μm;

[0111] (2) The phase change core material was transferred to a ceramic crucible, 23.17 g of attapulgite and 34.7 g of polyurethane were added and stirred evenly, and then placed in a 90°C hot water bath for heating and heat preservation for 30 minutes; then placed in a vacuum pot at -1.0 MPa for 20 minutes to obtain a pretreated material;

[0112] (3) Transfer the pretreated material to a 25mm*20mm*1.5mm mold for compression molding, wait for 12 hours at room temperature and then demold, to obtain a 25mm*20mm*1.5mm shaped phase change material.

[0113] Comparative Example 1

[0114] (1) 25.3 g of sodium acetate, 0.5 g of borax, 0.2 g of sodium polyacrylate, and 1.0 g of sodium methylcellulose were placed in a mortar and thoroughly mixed and ground to obtain a phase change core material with a particle size of 5 to 20 μm;

[0115] (2) The phase change core material was transferred to a ceramic crucible, 23 g of attapulgite and 34.7 g of molten polyethylene thermoplastic resin were added and stirred evenly, and then placed in a 90° C. hot water bath for heating and heat preservation for 30 min; then placed in a 0.6 MPa vacuum pot for evacuation for 20 min to obtain a pretreated material;

[0116] (3) Transfer the pretreated material to a 25mm*20mm*1.5mm mold for compression molding, wait for 12 hours at room temperature and then demold, to obtain a 25mm*20mm*1.5mm shaped phase change material.

[0117] The thermal conductivity, loading rate, phase change temperature and latent heat value of the shaped phase change materials in Examples 1-6 and Comparative Example 1 were tested. The thermal conductivity was obtained by the plate steady-state method; the loading rate is the percentage of other solids in the total weight except the binder, which can be calculated by formula; the phase change temperature was measured by differential scanning calorimeter (DSC) to obtain the initial point of phase change; the latent heat value was obtained by integrating the differential scanning calorimeter (DSC) measurement. The test results are shown in Tables 1 and Figure 1-Figure 7 As shown:

[0118] Table 1 Comparison of test results of different embodiments and comparative examples

[0119]

[0120] in, Figure 1-Figure 7 The differential scanning calorimeters are respectively the differential scanning calorimeters of Examples 1-6 and Comparative Example 1. Figure 1-Figure 7 It can be seen from Table 1 that, compared with Comparative Example 1, the shaped phase change material prepared in the embodiment of the present application has the advantages of high thermal conductivity, high load, high latent heat, etc.

[0121] The embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A shaped phase change material, characterized in that: It includes a porous skeleton and a phase change core material adsorbed on the porous skeleton; Wherein, the porous skeleton comprises a porous adsorbent and an adhesive, and the phase change core material comprises an energy storage material; The adhesive includes at least one of polyurethane, epoxy resin and silicone.

2. The shaped phase change material according to claim 1, characterized in that: The mass ratio of the porous adsorbent to the phase change core material is (1-3):(8-9).

3. The shaped phase change material according to claim 2, characterized in that: The mass ratio of the adhesive to the phase change core material is (1-3):(7-9).

4. The shaped phase change material according to any one of claims 1 to 3, characterized in that: The porous adsorbent includes at least one of activated carbon, biochar, diatomaceous earth, attapulgite, montmorillonite and graphene.

5. The shaped phase change material according to any one of claims 1 to 3, characterized in that: The polyurethane comprises at least one of a single-component polyurethane and a multi-component polyurethane; And / or, the silica gel includes at least one of single-component silica gel and multi-component silica gel.

6. The shaped phase change material according to any one of claims 1 to 3, characterized in that: The energy storage material includes at least one of nitrates, sulfates, carbonates, acetates, chlorides, bromides and borates.

7. The shaped phase change material according to claim 1, characterized in that: The phase change core material further includes at least one of a nucleating agent, a stabilizer and a thermal conductive aid.

8. The shaped phase change material according to claim 7, characterized in that: The mass ratio of the energy storage material to the thermal conductive additive is (8-10): (0-2).

9. The shaped phase change material according to claim 7, characterized in that: The nucleating agent comprises at least one of polyethylene, talc, mica, borax and phosphate; And / or, the stabilizer includes at least one of xanthan gum, sodium methyl cellulose and sodium polyacrylate; And / or, the thermal conductive additive includes at least one of carbon nanotubes, graphene, organic silicon compounds and nano oxides.

10. A method for preparing a shaped phase change material, for preparing the shaped phase change material according to any one of claims 1 to 9, characterized in that: include: Provide phase change core material; Mixing a porous adsorbent and a binder with the phase change core material to obtain a first mixture; The first mixture is subjected to a heating treatment and then subjected to a vacuum adsorption treatment to obtain a pretreated material; The pretreated material is transferred to a mold, subjected to compression molding and solidification, to obtain a shaped phase change material.

11. The method for preparing a shaped phase change material according to claim 10, characterized in that: After providing the phase change core material, the method further comprises: The phase change core material is ground to 5 μm-20 μm.

12. The method for preparing a shaped phase change material according to claim 10, characterized in that: The step of heating the first mixture comprises: Heating the first mixture at a first heating temperature for 20 min to 50 min; Wherein, the first heating temperature is T1, the highest phase change temperature of the energy storage material in the phase change core material is T2, and 30°C≤T1-T2≤50°C.

13. The method for preparing a shaped phase change material according to claim 10, characterized in that: The vacuum adsorption treatment comprises: The heated first mixture is maintained under a vacuum condition of 0.1 MPa-1.0 MPa for 15 min-30 min.

14. A shaped phase change material film, characterized in that: It includes a base film and a protective film wrapped around the base film; The base film is made of the fixed phase change material as described in any one of claims 1 to 9, and / or is made of the method for preparing the fixed phase change material as described in any one of claims 10 to 13.

15. The shaped phase change material film according to claim 14, characterized in that: The material of the protective film includes at least one of single-component polyurethane, multi-component polyurethane, epoxy resin, single-component silicone and multi-component silicone.